Schooner : building a wooden boat on Martha's Vineyard - Dunlop, Tom.; Shaw, Alison, 1953- (Edgartown, Mass. : Vineyard Stories, 2010)
This is the story of Ross Gannon and Nat Benjamin and the Gannon and Benjamin Marine Railway where the sailing vessel Rebecca was designed and built. Gannon and Benjamin is one of only a few full-time boatyards in the United States devoted exclusively to the design, construction, repair, and maintenance of traditional, plank-on-frame wooden boats. -- Publisher's description.
Includes bibliographical references (p. 159).
Keywords: Benjamin, Nat; Gannon, Ross; Gannon and Benjamin Marine Railway (Firm); Rebecca (Schooner); Rebecca (Schooner) -- Pictorial works; Wooden boats -- Design and construction; Wooden boats -- Design and construction -- Pictorial works; Schooners -- Design and construction; Schooners -- Design and construction -- Pictorial works; Boatbuilding -- Massachusetts -- Martha's Vineyard; Boatbuilding -- Massachusetts -- Martha's Vineyard -- Pictorial works